ANALISIS DAMPAK FAKTOR CUSTOMER RELATIONSHIP MANAGEMENT PADA PELANGGAN E-MARKETPLACE DI INDONESIA (STUDI KASUS: SHOPEE DAN BUKALAPAK) - Patty, Joanna Cristy (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
In this era of increasingly tight business development, many business competitors are required to be able to compete with their creativity. One important role in increasing business opportunities is to utilize available technology. The role of technology is very positive in supporting business processes for the company. Shopee and Bukalapak are one of the marketplace companies in Indonesia that implement Customer Relationship Management. Descriptive method will be used to assist this research and will begin with a survey and analysis of the comments contained in the Shopee and Bukalapak applications. The data obtained will be analyzed to see how much the level of customer confidence in Shopee and Bukalapak.